Green tax reform and employment: the interaction of profit and factor taxes - Stefan Boeters (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The employment effects of an ecological tax reform depend decisively on the presence of a profit tax and on the extent to which profits are taxed. This is shown in a model where firms have monopoly power on product markets and bargain over wages with unions on the labour market. In the setting, the value of the employment-maximising energy tax rate depends on the level of the profit tax. The question of wheather there is unemployment or not turns out to be less important.
Keywords: J51; H20; 330; factor taxes; profit taxes; ecological tax reform; trade unions; unemployment; Steuerreform; Ökosteuer; Lohnsteuer; Kapitalertragsteuer; Ertragsteuer; Steuerwirkung; Beschäftigungseffekt; Lohnverhandlungstheorie; Theorie